Attitudes Towards Transgender People Among Cisgender Women Who use Vaginismus and PCOS-related Online Forums. (1st August 2022) - Adams, O; Shindle, K; Gesselman, A; Campbell, J
ABSTRACT: Introduction: Polycystic ovary syndrome and vaginismus (V&PCOS) are two common chronic health problems that affect the wellbeing of 9 million or more American women. Women with V&PCOS often report significant delays in diagnosis and negative healthcare experiences. Women also report feeling that their gender expression or femininity is threatened by their condition, stemming predominantly from fertility problems or hirsutism complaints. Online forums for V&PCOS provide needed informational and emotional support, making these forums especially valuable for reducing disparities and increasing quality of life. However, these spaces may not be supportive for all. Informal observation of popular forums suggests frequent marginalization of transgender forum users by cisgender users-behaviors that may be linked to femininity threat. Objective: (1) survey cisgender women in V&PCOS online forums on their interactions with and perceptions of transgender individuals who also have these conditions; (2) investigate the link between the threats to feminine identity posed by V&PCOS and perceptions of transgender people with V&PCOS; (3) survey transgender people with V&PCOS on their condition(s), including the role of their own gender identity in their V&PCOS experiences, and their access to critically needed information and support on- and offline; and (4) explore any existing differences in the PCOS versus vaginismus online communities. Methods: An 85-item survey will be advertised on various V&PCOS online forums and related social media accounts. This survey includes ad-hoc items as well as validated scales. The ad-hoc items focus on online forum use experiences, including how active or passive participants are in their usage of these forums, their thoughts regarding the types of social support that the forums provide, their attitudes on the presence of transgender people in V&PCOS online forums, and their experiences seeking healthcare. The validated scales include the Transgender Knowledge, Attitudes, and Beliefs scale (TKAB); the 12-item Short Form Health Survey (SF-12); and selections from the Polycystic Ovary Quality of Life scale (PCOS-QoL). The survey also includes the Implicit Attitudes Test, and is calibrated to measure transgender vs. cisgender bias. Demographic items are also included (e.g., gender, sex assigned at birth, education level, sexual orientation, relationship status, race, ethnicity). Results: The research team hypothesizes that cisgender women who report more negative attitudes towards transgender people in the TKAB as well as the transgender IAT will also report more negative attitudes regarding the presence of transgender people in V&PCOS health forums. Similarly, the team also predict that high scores on femininity threat measures may be positively associated with negative attitudes towards transgender people. The research team also hypothesizes that transgender people may report more difficulty in finding a supportive environment within V&PCOS forums given the social stigma attached to transgender identity. Conclusions: Online forums represent an alternative source of information and support where formal healthcare systems falter. Examining the attitudes towards transgender people in these communities, the experiences of transgender people in them, and the intersecting consequences will help to deepen our understanding of how these communities operate for all people dealing with V&PCOS, regardless of gender. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Match Group